Code Mixing Analysis in Group Discussion Activitiy in Speaking Class - siska, siska; Yelliza, Yelliza (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The aim of this research was to figure out the code mixing that existed in English communication among the students while doing group discussion and to classify the types of code mixing that occurred during this speaking activity. Actually, code mixing may probably happens while English is being taught as the foreign language since we have Indonesian as our first language so that the concept of bilingualism could be built among Indonesian students. For example, the English students of Universitas PGRI Sumatera Barat in 2021 Academic year, as the subjects of this research, used code mixing during the speaking activity although most of them are good enough in English. This phenomenon became the big concern for the researchers to do this research by using descriptive qualitative design, because the researchers need to analyze and to describe the types of code mixing. The data of this research are all utterances of code mixing used by the students during the discussion. The instruments were observation, field note and recording. After analyzing the data, the researchers found that there are three main types of code mixing; insertion, alternation and congruent, used by the students while doing discussion. It is hoped that the result of this research make all the teachers aware that the fluency of speaking English could not be obtain since the students allow their mother tongue interfere their English so that the teachers should find out the strategies to avoid code mixing among the students while doing speaking activities.